Pullback Attractor for a Non-Autonomous Generalized Cahn-Hilliard Equation with Biological Applications. Issue 3 (3rd May 2016) - Duan, Ning
Abstract: In this paper, we consider a non-autonomous generalized Cahn-Hilliard equation with biological applications. It is shown that a pullback attractor of the equation exists when the external force has exponential growth.